Keaktifan Siswa Melalui Model Pembelajaran Project Based Learning Berbasis TPACK - Iyul Yulyaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In achieving the quality of learning currently teachers are required to implement innovative learning by utilizing relevant technology. The aim of this research is to increase students' activeness in participating in chemistry lessons using the TPACK-based Project Based Learning model. The research was conducted qualitatively using descriptive methods in class XI chemistry learning using the 2013 Curriculum on Natural Acid Base Indicators material. Based on the results of observations, it is known that all indicators of student activity measured reached a minimum of 80%. This shows that the application of TPACK-based Project Based Learning can increase student activity in learning chemistry.